Pengaruh Promosi Kesehatan Menggunakan Roda Kecerdasan (Roked) Terhadap Perilaku Pencegahan Gastritis di SMP N 1 Liwa - Nuri Marantika; Dwi Yulia Maritasari; Rustika Rustika (Puslitbang Sinergis Asa Professional, 2025)
One of the most common gastrointestinal health problems among students is gastritis. Gastritis can become a peptic ulcer, which eventually causes impacts such as bleeding, peritonitis, or even death. The survey results at SMP N 1 Liwa found that 61% of students did not know a good diet to prevent gastritis. Prevention efforts are carried out by increasing a person's knowledge, attitude, and diet through health promotion efforts, one of which uses intelligence wheel media (Roked). The purpose of this study was to determine the effect of health promotion using the wheel of intelligence (Roked) on knowledge, attitudes, and diet to prevent gastritis at SMP N 1 Liwa. This study is a quantitative study that uses the Quasy experiment method with a one group pretest-postest research design with control group. Intervention in the form of providing health promotion using intelligence wheel media (Roked). The sample in the study were students with a history of gastritis symptoms at SMP N 1 Liwa, as many as 36 people in the intervention group and 36 people in the control group using purposive sampling technique. The research instrument was a pretest and posttest questionnaire with data analysis using Paired sample T-test and Independent sample T-test. The results of the analysis showed there was a difference in the mean score of knowledge (p=0.000), attitude (p=0.000), diet (p=0.000) before and after given health promotion using the wheel of intelligence media (Roked). The results of this study indicate the influence of health promotion using the wheel of intelligence media (Roked) on knowledge p=0.024, attitude p=0.012, diet p=0.036 for the for the prevention of gastritis in SMP N 1 Liwa. We recommend that the wheel of intelligence (Roked) media can be used as an alternative in health promotion that is routinely carried out in convey information about gastritis prevention.